Human neural stem cell transplantation into the corpus callosum of Alzheimer's mice. Issue 10 (18th August 2017) - McGinley, Lisa M.; Kashlan, Osama N.; Chen, Kevin S.; Bruno, Elizabeth S.; Hayes, John M.; Backus, Carey; Feldman, Seth; Kashlan, Bader N.; Johe, Karl; Feldman, Eva L.
Abstract: The hippocampus has been the target of stem cell transplantations in preclinical studies focused on Alzheimer's disease, with results showing improvements in histological and behavioral outcomes. The corpus callosum is another structure that is affected early in Alzheimer's disease. Therefore, we hypothesize that this structure is a novel target for human neural stem cell transplantation in transgenic Alzheimer's disease mouse models. This study demonstrates the feasibility of targeting the corpus callosum and identifies an effective immunosuppression regimen for transplanted neural stem cell survival. These results support further preclinical development of the corpus callosum as a therapeutic target in Alzheimer's disease.